(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In 1995-96, a study was carried out in Eastern Sicily on the biology and ethology of Aleurolobus teucrii Mifsud & Palmeti, that lives on Teucrium fruticans L. (Labiatae). The whitefly has two yearly generations, with adults flying in May-June and July-August; it overwinters in the nymphal stages, especially 3rd and 4th instars, and its development only slightly slows down during the coldest months. Natural mortality at pre-imaginal stages was quite modest throughout the study. Parasitization by Encarsia olivina (Masi) (Hymenoptera Aphelinidae) was frequently observed, though usually at moderate levels. Direct contro! of the whitefly is not thought to be necessary at present, in spite of the increasing commerciai interest in its host plant.